Effect Of Online Promotion, Price And Brand Image On Purchase Decisions For Neosaipress Herbal Products - Adi Suparwo (Institute of Computer Science (IOCS), 2022)
Purchasing decisions are one of the keys for companies to gain profits. For that we need the right marketing strategy for the company so that consumers can buy the products offered. This study aims to determine the effect of online promotion, price and brand image on purchasing decisions for Neosaipress herbal products. The analytical technique used to analyze the effect of the variables in this study is using multiple regression analysis, t test and F test. The population used is Neosaipress product consumers at PT. Penawar Legenda Maju who shopped at Bandung Stockist. With the sample obtained, namely 80 respondents. The results showed that online promotion and brand image partially influence purchasing decisions, while price does not partially affect purchasing decisions. Simultaneously online promotion, price and brand image affect the purchase decision of Neosaipress products. Based on the results of the study, the company must improve its marketing strategy which is considered not optimal, in order to achieve increased purchasing decisions